FACTORS THAT AFFECTED COLLABORATIVE GOVERNANCE IN SPATIAL PLANNING OF DEPOK CITY - David Saputra; Irfan Ridwan Maksum (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The aims of the study are to analyse the factors that affected collaborative governance and also efforts to build collaborative governance in spatial planning in the city of Depok. This research used qualitative method with post-positivist approach. The data collection method consists of (1) Primary data which were collected through in-depth interviews with Public Works and Spatial Planning Department of Depok city; Development Planning Board of Depok city; and stakeholders in Depok related to the research problem such as housing developers and social society. (2) Secondary data were collected through the literature and documentation at the Public Works and Spatial Planning Department in Depok city.According to Indonesian laws and regulations Article 26 of 2007 on Spatial Planning, each city in Indonesia is required to have a Green Open Space (GOS) of at least 30 percent of its territory. It is also purposed to increase cooperation of all elements for Depok’s spatial planning.This research indicates that the implementation of collaborative governance in Depok’s spatial planning has not been effective because Depok only has 3227.26 ha GOS less than 30 percent of 202.9 KM² city wide; the economic centralization in one particular region should have been intended for office or municipal services; and the role of government is still dominant in cooperation with stakeholders in spatial planning and management through public discussion, public hearing, and public consultation. Such a condition is influenced by several factors: lack of networked structure; lack of distributive accountability/ responsibility; and the lack of trust among the participants in spatial planning of Depok city. Keywords: collaborative governance, good governance, spatial planning, green open space